2022
DOI: 10.3390/life12122063
|View full text |Cite
|
Sign up to set email alerts
|

High Post-Treatment Leptin Concentration as a Prognostic Biomarker of the High Risk of Luminal Breast Cancer Relapse: A Six-Year Comprehensive Study

Abstract: (1) Background: Nowadays, obesity is well-recognised as a significant risk factor for many chronic diseases, for example, hypertension, diabetes, atherosclerosis and cancer. This study is designed to investigate the prognostic value of the pre- and post-treatment serum levels of adiponectin and leptin in luminal A and B invasive breast cancer (IBrC) patients based on six-years follow-up. (2) Methods: Among 70 patients who underwent breast surgery, 35 were Stage I and 35 were Stage II. The concentrations of pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Elevated leptin expression in breast cancer is indicative of a more aggressive cancer phenotype and is associated with tumor size, lymph node involvement, and metastasis [91]. Katarzyna et al found that post-treatment serum leptin concentration may be associated with the prognosis of early stage luminal invasive breast cancer and can be used as a prognostic indicator [92]. The influence of leptin on tumor-associated macrophages (TAMs) is intriguing.…”
Section: Leptinmentioning
confidence: 99%
“…Elevated leptin expression in breast cancer is indicative of a more aggressive cancer phenotype and is associated with tumor size, lymph node involvement, and metastasis [91]. Katarzyna et al found that post-treatment serum leptin concentration may be associated with the prognosis of early stage luminal invasive breast cancer and can be used as a prognostic indicator [92]. The influence of leptin on tumor-associated macrophages (TAMs) is intriguing.…”
Section: Leptinmentioning
confidence: 99%